Large-scale scientific computing : 12th International Conference, LSSC 2019, Sozopol, Bulgaria, June 10-14, 2019, Revised selected papers /: 12th International Conference, LSSC 2019, Sozopol, Bulgaria, June 10-14, 2019, Revised selected papers. (2020) - Unknown
No abstract available